Risk factors of Early Shedding of Deciduous Teeth in Children under Five Years - Asad, Abul Kalam Mohammad; Sabnom, Rumana; Saud, Nur E; Parvin, Ayrin; Rahman, Md Shoyeb; Islam, Md Shahidul (TAJ: Journal of Teachers Association, 2021)
A descriptive cross-sectional study was undertaken in Shimul Memorial North-South School Laxmipur Branch, Rajshahi. Among the children aged under five years with premature or early tooth loss or shedding. In order to find out the relationship between early shedding of deciduous teeth and selected dental conditions like dental caries, dental trauma, etc., and socioeconomic background. In this study, out of 110 children, 61 (55.5%) were male, and 49 (44.5%) were female. It was observed that the highest number of children, 109 (99.1%), were Muslim and 1 (0.9%) was Hindu. Among all the parents of children, 6 (5.5%) were educated up to primary level, and 33(30%) were masters and above. Regarding monthly family income, 2 (1.8%) had Tk. 5000-8000 and 15 (13.6%) parents had Tk. 15000-18000. The majority (66.4%) of the children under study were found to clean teeth only once daily. Tooth cleaning by toothbrush & paste and frequency was once daily73 (66.4%). Children liked more sugar-containing food 89 (80.9%) and used to take milk at bedtime (42.7%). The majority of the respondents had intake carbohydrate 91 (82.7%) containing food and the majority of the respondents, 61 (65.5%), had dental caries. A significant association was found between dental carries and shedding of deciduous teeth, but no association was found between sugar- containing food and shedding of teeth. TAJ 2021; 34: No-1: 97-105